The Influence of Service Quality and Store Atmosphere on Customer Satisfaction at the Starbucks Pakuwon Mall Surabaya Outlet - Yuda Agus Prasetyo; Hery Pudjoprastyono (PT Inovasi Pratama Internasional, 2023)
This research aims to determine the partial influence of the Customer Satisfaction and Store Atmosphere variables on Customer Satisfaction at the Starbucks Pakuwon Mall Surabaya Outlet. This type of research is quantitative. The population in this research is Starbucks consumers in Pakuwon Surabaya, namely aged 17 years and over who live in Surabaya and have made purchases at Starbucks Pakuwon Mall Surabaya. The sample for this research consisted of 91 respondents. The sampling technique used in this research is non-probability sampling (STB). Data collection using questionnaires as the primary research data source. Meanwhile, the data processing technique used is Partial Least Square (PLS). Based on the research results, it can be concluded that Service Quality has a significant positive effect on Customer Satisfaction, Store Atmosphere has a positive effect on Customer Satisfaction.